2018
DOI: 10.1007/s00253-018-9062-x
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing displayed proteins on vegetative Bacillus subtilis cells

Abstract: Microbes engineered to display heterologous proteins could be useful biotechnological tools for protein engineering, lignocellulose degradation, biocatalysis, bioremediation and biosensing. Bacillus subtilis is a promising host to display proteins, as this model Gram-positive bacterium is genetically tractable and already used industrially to produce enzymes. To gain insight into the factors that affect displayed protein stability and copy-number, we systematically compared the ability of different protease-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…2008; Huang et al . 2018). Moreover, the C‐terminal end of molecular chaperon prsA of B. subtilis fused with Clostridium thermocellum cellulase (celA) can make more than 85% of total cellulase activity be in surface‐displayed format (Kim et al .…”
Section: Probiotics Surface Display Systemmentioning
confidence: 99%
“…2008; Huang et al . 2018). Moreover, the C‐terminal end of molecular chaperon prsA of B. subtilis fused with Clostridium thermocellum cellulase (celA) can make more than 85% of total cellulase activity be in surface‐displayed format (Kim et al .…”
Section: Probiotics Surface Display Systemmentioning
confidence: 99%
“…Even though this section focused on eukaryotic models, it is worth noting that several approaches were also taken in prokaryotic hosts to pursue a more efficient protein secretion and display, given that purification of such enzymes is often troublesome due to the typical formation of inclusion bodies in these systems [126]. Works by Yildirim et al, in which a recombinant endoglucanase was efficiently engineered for periplasmic and extracellular targeting by a native secretion signal of E. coli [138], and Huang et al, who showed the advantages of using protease-deficient strains of B. subtilis for cell-surface display of heterologous endoglucanase [139], gave insights for overcoming current limitations of prokaryotic systems.…”
Section: Protein Engineeringmentioning
confidence: 99%